Metaverse-Based Demonstrators as an Alternative to Traditional Presentations: Case Fossil-Free Steelmaking Processes - Immonen, Tommi; Nirhamo, Eero; Salonen, Mikko; Seppälä, Kaapo; Helle, Seppo; Heimo, Olli; Lehtonen, Teijo (United States, 2026)
In recent years, metaverse platforms have developed to the point where they are expected to become a new revolutionary marketing tool. This paper provides a case study of their use as a powerful alternative to traditional presentation means. An enterprise-targeted, standalone metaverse experience was developed with Microsoft Mesh to compare two different steelmaking processes of a major company in the industry participating in a maritime project. The developed experience was tested on several occasions in systematically controlled environments, involving 22 participants, all of whom were either affiliated with the maritime industry or academic researchers working with the maritime industry. The participants were asked to complete a user feedback survey after testing the experience. Based on both observational data and the survey responses gathered, it was evident that metaverse solutions built for informative purposes could significantly improve or even replace traditional means to showcase otherwise complex processes.
Keywords: Virtual reality, Metaverse, Steelmaking, Marketing, Communication, Sustainability, Process visualization
Accessibility, Assistive Technology and Digital Environments : Proceedings of the 16th International Conference on Applied Human Factors and Ergonomics and the Affiliated Conferences, Orlando, Florida, USA 26-30 July 2025